Integrated Transcriptomic and Proteomic Analysis Reveals Up-Regulation of Apoptosis and Small Heat Shock Proteins in Lens of Rats Under Low Temperature - Zhou, Jiayue; Wu, Jing; Zheng, Sifan; Chen, Xiangjun; Zhou, Daizhan; Shentu, Xingchao (Frontiers in Physiology, 2021)
Cold cataract is the reversible opacification of the lens when the temperature decreases. However, we observed that when temperature of the rats’ lens was maintained at a lower temperature for a prolonged time, the opacification of lens was only partly reversible. To review the potential molecular mechanism of the irreversible part of opacification under cold stimulation, we applied comparative transcriptomic and proteomic analysis to systematically investigate the molecular changes that occurred in the lens capsules of rats under low temperature treatments. The RNA sequencing based transcriptomic analysis showed a significant up-regulation of genes related to the lens structure and development in the Hypothermia Group. Hub genes were small heat shock proteins (sHSPs). Besides the same findings as the transcriptomic results, the liquid chromatography-tandem mass spectrometry based proteomic analysis also revealed the up-regulation of the apoptotic process. To further analyze the regulatory mechanism in this process, we subsequently performed integrated analysis and identified the down-regulation of Notch3/Hes1 and PI3K/Akt/Xiap signaling axis. Our research revealed the activation of the apoptotic process in rats’ lens under cold stimulation, and the sHSP related heat shock response as a potential protective factor through our transcriptomic and proteomic data.